Mitochondrial Ca2+-handling in fast skeletal muscle fibers from wild type and calsequestrin-null mice. - Michele Scorzeto; Marta Giacomello; Luana Toniolo; Marta Canato; Bert Blaauw; Cecilia Paolini; Feliciano Protasi; Carlo Reggiani; Ger J M Stienen (PLoS ONE)
Mitochondrial calcium handling and its relation with calcium released from sarcoplasmic reticulum (SR) in muscle tissue are subject of lively debate. In this study we aimed to clarify how the SR determines mitochondrial calcium handling using dCASQ-null mice which lack both isoforms of the major Ca(2+)-binding protein inside SR, calsequestrin. Mitochondrial free Ca(2+)-concentration ([Ca(2+)]mito) was determined by means of a genetically targeted ratiometric FRET-based probe. Electron microscopy revealed a highly significant increase in intermyofibrillar mitochondria (+55%) and augmented coupling (+12%) between Ca(2+) release units of the SR and mitochondria in dCASQ-null vs. WT fibers. Significant differences in the baseline [Ca(2+)]mito were observed between quiescent WT and dCASQ-null fibers, but not in the resting cytosolic Ca(2+) concentration. The rise in [Ca(2+)]mito during electrical stimulation occurred in 20-30 ms, while the decline during and after stimulation was governed by 4 rate constants of approximately 40, 1.6, 0.2 and 0.03 s(-1). Accordingly, frequency-dependent increase in [Ca(2+)]mito occurred during sustained contractions. In dCASQ-null fibers the increases in [Ca(2+)]mito were less pronounced than in WT fibers and even lower when extracellular calcium was removed. The amplitude and duration of [Ca(2+)]mito transients were increased by inhibition of mitochondrial Na(+)/Ca(2+) exchanger (mNCX). These results provide direct evidence for fast Ca(2+) accumulation inside the mitochondria, involvement of the mNCX in mitochondrial Ca(2+)-handling and a dependence of mitochondrial Ca(2+)-handling on intracellular (SR) and external Ca(2+) stores in fast skeletal muscle fibers. dCASQ-null mice represent a model for malignant hyperthermia. The differences in structure and in mitochondrial function observed relative to WT may represent compensatory mechanisms for the disease-related reduction of calcium storage capacity of the SR and/or SR Ca(2+)-leakage.